The alchemist - Coelho, Paulo (Harper, 2006)
Paulo Coelho's masterpiece tells the magical story of Santiago, an Andalusian shepherd boy who yearns to travel in search of a worldly treasure as extravagant as any ever found. The story of the treasures Santiago finds along the way teaches us, as only a few stories can, about the essential wisdom of listening to our hearts, learning to read the omens strewn along life's path, and, above all, following our dreams.